Ecolabeling, Green Advertising, and Branding: Drivers of Green Purchasing Behavior Among Generation Z - Amaris Sih Kinanthi; Damayanti Octavia (Binus Business Review, 2025)
Generation Z is highly aware of sustainability and environmental issues, yet skepticism toward sustainability claims and the prioritization of product quality and price pose challenges to green marketing effectiveness. The research examined the influence of green marketing strategies on Generation Z’s consumer behavior in influencing green purchasing behavior. It explored three key elements of green marketing: ecolabeling, green advertising, and green branding. It also assessed the mediating roles of environmental knowledge and green consumption in shaping green buying behavior. A quantitative survey was conducted among 400 Generation Z consumers in Indonesia, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that green marketing strategies significantly impact environmental knowledge, which subsequently influences green consumption and green buying behavior. Transparency in sustainability claims, clear communication of product benefits, and consumer education on environmental issues are essential in fostering trust and engagement. The research offers originality by integrating environmental knowledge and green consumption as mediators in a Generation Z context, providing new empirical insights into how green marketing strategies influence this demographic. It contributes theoretically to consumer behavior literature and offers practical implications for businesses to design marketing strategies that appeal to environmentally conscious consumers. Companies aiming to attract Generation Z must prioritize transparency, consumer education, and engagement to build trust and long-term loyalty. Future research can explore the role of digital marketing and social media in enhancing green consumerism among younger generations.